Cloud versus Edge Computing in the Pharmaceutical Environment : A Decision-Making Framework for Regulated Environments - Laiho, Antton (My University, 2025)
As the pharmaceutical industry is adapting the principles from Industry 4.0 to Pharma 4.0 and at the same time researching the possibilities of new technologies such as artificial intelligence and machine learning in its highly regulated operating environment, the increasing amount of data that is collected from the manufacturing and business processes present many challenges. These challenges are not only coming from global and domestic regulation entities regarding e.g., computerized systems, GMP and data integrity. But also, from the usability of the data, regulatory adherence, and the technical challenges that the solutions itself have such as scalability, data privacy, latency and cost-efficiency All of these affect the decision-making regarding the computational solutions to be implemented. This research aims to answer the research questions and to build decision-making framework to assist and standardise the decision-making process when Cloud and Edge computing solutions are evaluated and compared in highly regulated pharma environment.
Keywords: AI, Cloud, Computing, Edge, Fog, GAMP, GMP, GxP, IoT, Industry 4.0, LLM, Pharma 4.0, Pharma